The Impact of In-Store Dining Experience on Brand Attraction and Customer Loyalty: Evidence from IKEA - Gan Kia Hui; Oh Zi Jian; Kiara Wong Mann Mann; Khor Yong Wen; Kong Yi Wen; Kua Zi Jian; Pratibha Vishnoi; Daisy Mui Hung Kee (International Journal of Tourism and Hospitality in Asia Pasific, 2026)
This study investigates how in-store dining experience influences brand attraction and customer loyalty in a non-food-dominant retail context, using IKEA as a case study. Grounded in the Stimulus–Organism–Response (SOR) model and Experiential Marketing Theory, the study examines the role of dining experience as a stimulus that shapes brand attraction and subsequent loyalty. A quantitative survey was conducted among 204 IKEA customers in Malaysia, and the data were analysed using descriptive statistics and multiple regression analysis. The findings reveal that dining experience has a significant positive effect on brand attraction, while brand attraction strongly predicts customer loyalty. The regression model explains 63.5% of the variance in customer loyalty, with brand attraction emerging as the dominant predictor. These results demonstrate that in-store dining functions as a strategic experiential touchpoint that enhances emotional brand connection and strengthens long-term loyalty. The study provides managerial insights for retailers seeking to leverage dining services to reinforce brand engagement and customer retention.